NCBP1 promotes the development of lung adenocarcinoma through up‐regulation of CUL4B. Issue 10 (26th August 2019) - Zhang, Huijun; Wang, An; Tan, Yulong; Wang, Shaohua; Ma, Qinyun; Chen, Xiaofeng; He, Zelai
Abstract: Lung cancer is the most frequent cancer type and is the leading cause of tumour‐associated deaths worldwide. Nuclear cap‐binding protein 1 (NCBP1) is necessary for capped RNA processing and intracellular localization. It has been reported that silencing of NCBP1 resulted in cell growth reduction in HeLa cells. Nevertheless, its clinical significance and underlying molecular mechanisms in non–small‐cell lung cancer remain unclear. In this study, we found that NCBP1 was significantly overexpressed in lung cancer tissues and several lung cancer cell lines. Through knockdown and overexpression experiments, we showed that NCBP1 promoted lung cancer cell growth, wound healing ability, migration and epithelial‐mesenchymal transition. Mechanistically, we found that cullin 4B (CUL4B) was a downstream target gene of NCBP1 in NSCLC. NCBP1 up‐regulated CUL4B expression via interaction with nuclear cap‐binding protein 3 (NCBP3). CUL4B silencing significantly reversed NCBP1‐induced tumorigenesis in vitro. Based on these findings, we propose a model involving the NCBP1‐NCBP3‐CUL4B oncoprotein axis, providing novel insight into how CUL4B is activated and contributes to LUAD progression.